Toxic Responses Induced at High Doses May Affect Benchmark Doses - Jürg A. Zarn; Ursina A. Zürcher; H. Christoph Geiser (SAGE Publishing, 2020)
To derive reference points (RPs) for health-based guidance values, the benchmark dose (BMD) approach increasingly replaces the no-observed-adverse-effect level approach. In the BMD approach, the RP corresponds to the benchmark dose lower confidence bounds (BMDLs) of a mathematical dose-response model derived from responses of animals over the entire dose range applied. The use of the entire dose range is seen as an important advantage of the BMD approach. This assumes that responses over the entire dose range are relevant for modeling low-dose responses, the basis for the RP. However, if part of the high-dose response was unnoticed triggered by a mechanism of action (MOA) that does not work at low doses, the high-dose response distorts the modeling of low-dose responses. Hence, we investigated the effect of high-dose specific responses on BMDLs by assuming a low- and a high-dose MOA. The BMDLs resulting from modeling fictitious quantal data were scattered over a broad dose range overlapping with the toxic range. Hence, BMDLs are sensitive to high-dose responses even though they might be irrelevant to low-dose response modeling. When applying the BMD approach, care should be taken that high-dose specific responses do not unduly affect the BMDL that derives from low doses.